2020
DOI: 10.5586/aa.7343
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity and Population Structure of Tunisian Barley Accessions (Hordeum vulgare L.) Using SSR Markers

Abstract: In barley breeding programs, information about genetic dissimilarity and population structure is very important for genetic diversity conservation and new cultivar development. This study aimed to evaluate the genetic variation in Tunisian barley accessions (<em>Hordeum</em><em> </em><em>vulgare </em>L.) based on simple sequence repeat (SSR). A total of 89 alleles were detected at 26 SSR loci. The allele number per locus ranged from two to five, with an average of 3.4 allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The 32 barley used in this study were evaluated for morphological traits, grain yield, yield components and physiological traits. These traits are targeted to increase the genetic variability and thus selection in barely breeding programs [31]. In addition, assessing genetic diversities is important in identifying genotypes with good phenotypic traits [32] and distinct genetic groups [33].…”
Section: Discussionmentioning
confidence: 99%
“…The 32 barley used in this study were evaluated for morphological traits, grain yield, yield components and physiological traits. These traits are targeted to increase the genetic variability and thus selection in barely breeding programs [31]. In addition, assessing genetic diversities is important in identifying genotypes with good phenotypic traits [32] and distinct genetic groups [33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, systematic relationships between barley families were examined using ISSR, SRAP, and ISTR data to determine molecular phylogeny, with ISTR and SRAP markers showing good discriminating power for defining genetic variation [ 36 ]. Similarly, TRAP markers distinguished agricultural types effectively, while the SRAP marker dendrogram classified Egyptian barley cultivars into distinct groups based on genetic similarity coefficients [ 53 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clusters consisted of distinct cultivars that were found to be unevenly distributed. Cluster 1 was mainly composed of cultivars like Rihane and Lemsi, while Cluster 2 featured cultivars like Kounouz and Manel [ 53 ]. Similarly, analysis by Mohammadi et al indicated a peak delta K value at K = 3, supporting categorizing populations into three major subpopulations corresponding to Iranian landraces, foreign landraces, and varieties and advanced breeding lines [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the higher gene flow across geographic regions and the variation among accessions was more important than looking for differences in geographic regions as a source of genetic distance among accessions to use in barley breeding programs. Other researchers also studied the population structure of barley genotypes and reported that there was more genetic variation among individuals within a population than among populations [ 13 , 37 , 63 ].…”
Section: Discussionmentioning
confidence: 99%